Relevance of The Local Wisdom of Ki Hajar Dewantara’s teachings with Pancasila Values and Islamic Morality - Warsito, Warsito; Aji, Wisnu Nugroho; Widodo, Sudiyo; Nur’aini, Dhiva Maulida Rizqi (Proceedings of International Conference on Science, Education, and Technology, 2025)
The era of globalization not only brings positive but also negative impacts. Technological advances are useful for facilitating human work, but can also be destructive. This study aims to 1) describe the local wisdom of the teachings of Ki Hajar Dewantara which is relevant to the values ​​of Pancasila and Islamic morality, 2) find the reasons why the local wisdom of the teachings of KHD is relevant to the values ​​of Pancasila and Islamic morality. This study applies a descriptive method. This study uses data sources 1) key informants, the chairman and manager of the DKG Museum Yogyakarta, character education experts, and religious experts, 2) a collection of KHD letters at the DKG Museum Yogyakarta, 3) events in the form of micro films. Data collection uses in-depth interviews, observation, documentation, and content analysis. Triangulation technique for checking the validity of data. Interactive analysis technique in the form of Components of Data Analysis. The results of the study show 1) There are at least 12 local wisdoms of KHD teachings that are relevant to the values ​​of Pancasila and Islamic morality, 2) The reasons why the local wisdom of KHD teachings is relevant to the values ​​of Pancasila and Islamic morality. This finding is important in efforts to elevate the nobility of the values ​​of Pancasila and Islamic morality.